Phototropism: Mechanism and Outcomes - Pedmale, Ullas V. (American Society of Plant Biologists, 2010)
Plants have evolved a wide variety of responses that allow them to adapt to the variable environmental conditions in which they find themselves growing. One such response is the phototropic response - the bending of a plant organ toward (stems and leaves) or away from (roots) a directional blue light source. Phototropism is one of several photoresponses of plants that afford mechanisms to alter their growth and development to changes in light intensity, quality and direction. Over recent decades much has been learned about the genetic, molecular and cell biological components involved in sensing and responding to phototropic stimuli. Many of these advances have been made through the utilization of Arabidopsis as a model for phototropic studies. Here we discuss such advances, as well as studies in other plant species where appropriate to the discussion of work in Arabidopsis.